Disruption of polystyrene latex aggregates in capillary flow - Tang, S.; McFarlane, C. M.; Zhang, Z. (Colloid and polymer science, 2000)
Disruption of polystyrene latex aggregates, formed in 1M citric acid/phosphate buffer solution at pH 3.8 through diffusion-limited colloid aggregation (DLCA) and in 0.2M NaCl solution at pH 5.5 through reaction-limited colloid aggregation (RLCA), was studied with respect to aggregate size and fractal nature. This was achieved using small-angle laser scattering in conjunction with a specially designed sampling method, which brought about the elimination of the disruption of the aggregates caused by a commercial stirrer sample unit. Aggregations were carried out in a mixture of deuterium oxide and water instead of water alone as a solvent to minimise sedimentation resulting from the differences in density between the latex particles and the electrolytes. An initial "steady state" in terms of aggregate size and fractal dimension was found to occur after around 20min and 2 days for DLCA and RLCA aggregates, respectively, at 25°C. No aggregate disruption was detected for DLCA and RLCA aggregates after their passing through a capillary tube for shear rates up to 1584 and 2694 s^sup -1^, respectively. At higher shear rates, significant decreases in the aggregate volume-mean diameter, D[4,3], occurred after shearing. The degree of reduction in D[4,3] was larger for DLCA aggregates in comparison to RLCA aggregates. The results would suggest that DLCA aggregates were more subject to disruption during shearing. A high degree of disruption was observed in turbulent flow for both aggregates.[PUBLICATION ABSTRACT]